Implementasi Sistem Pengukuran Kepuasan Masyarakat Berbasis Kuesioner Pada Pelayanan Publik Di Desa Mano'an. - Fatli, Fatli; Budhi, Robby Kurniawan; Widianto, Yonatan (JATISI, 2025)
Community contentment serves as a significant measure for evaluating the standard of public services within villages. However, in Mano’an Village, the satisfaction measurement process is still carried out in an unstructured manner, such as through verbal complaints, which does not produce valid data for evaluation and decision-making. This study develops a questionnaire-based community satisfaction measurement system to provide a more objective, directed, and well-documented assessment mechanism. The system is designed to systematically collect data from various types of village services, including administrative, health, education, infrastructure, land affairs, security, and social services. The introduction of an online system allows the village administration to handle information, conduct assessments, and generate clear and straightforward reports. The findings indicate that the system enhances the efficiency of evaluating public services, help the village government understand community needs, and assist in determining service improvement priorities. In addition, the availability of structured data supports transparency, accountability, and increased community participation in village development. Overall, this system is expected to serve as a strategic tool for improving the quality of public services and village governance